The Relationship Between Colonoscopy Procedure Order and Adenoma Detection Rates: A Prospective Study. Issue 8 (September 2015) - Kang, Hae Yeon; Kim, Donghee; Kim, Hwa Jung; Kang, Seung Joo; Chung, Goh Eun; Song, Ji Hyun; Yang, Sun Young; Kim, Young Sun; Park, Min Jung; Yim, Jeong Yoon; Lim, Seon Hee; Kim, Joo Sung
Abstract : Goals: The aim of this study was to prospectively assess the effects of the order of colonoscopic procedures and other possible factors on the adenoma detection rate (ADR). Background: There have been conflicting studies regarding the timing or order of a colonoscopy and its ability to detect adenomas. Study: Between March 2011 and July 2011, consecutive colonoscopies were prospectively performed by 7 board-certified staff endoscopists at the Seoul National University Hospital Healthcare System Gangnam Center. The primary outcome was the overall ADR according to the procedure order of the colonoscopies, and the secondary outcome was the identification of other possible factors influencing the ADR. Results: A total of 1908 colonoscopies were analyzed. The detection rate was 56.5% for all polyps and 37.3% for adenomas. The ADR increased as the performance order of the colonoscopy increased and was highest for the third procedure (43.4%). However, the ADR of the remaining procedures, including later procedures, was similar throughout the workday. In the multivariable analysis, the ADR was significantly associated with older age, male sex, high body mass index, personal history of colorectal polyps, long withdrawal time, and an experienced endoscopist. However, the colonoscopy procedure order was not significantly associated with the ADR. Conclusions: The ADR was stable according to the procedure order for the later procedures of the workday in a setting of moderate daily procedure volumes. The withdrawal time and experience level of the endoscopist were more important than the procedure order in detecting adenomas by colonoscopy.